Increased corrosion resistance of steel substrates coated with epoxy resin/ZnO/Fe2O3 obtained from electric arc furnace dust recovery - Mário Andrean Macedo Castro; Tanara Caroline Nunes Nicácio; Antonio Carlos do Nascimento Santos; José Eudes Lima Santos; Luis David Loor-Urgilés; Antonio Eduardo Martinelli; Fabiana Villela da Motta; Mauricio Bomio (Journal of Materials Research and Technology)
The sustainable management of metal-rich industrial wastes, such as electric arc furnace dust (EAFD), remains a critical challenge for the steel industry. Although previous studies have investigated metal recovery routes and their application in functional materials, few have explored the reuse of these wastes as active components in anticorrosive coatings. This work proposes an innovative approach for valorizing EAFD, recovering iron (Fe2O3) and zinc (ZnO) oxides through acid leaching, basic precipitation, and heat treatment. After recovery, mixed ZnO/Fe2O3 oxides were prepared in different proportions and incorporated as nanofillers in an epoxy matrix, creating a hybrid coating aimed at protecting carbon steel against corrosion. The obtained materials were characterized by XRF, XRD, FTIR, SEM, and BET analysis, while the mechanical and anticorrosive properties were evaluated by Vickers hardness tests, Potentiodynamic Polarization and Electrochemical Impedance Spectroscopy. After 240 h of immersion in saline solution and 360 h of Salt-spray test, the coating with the highest Fe2O3 content demonstrated superior performance, reducing the corrosion rate by up to 100 times and increasing the load transfer resistance by up to 80 times. The contribution of this study lies in both the proposal of a new cycle for reusing steel waste and in demonstrating a viable route for developing high-performance anticorrosive coatings with potential for industrial application in sectors such as oil and gas. The combination of waste recovery and functional improvement of the material positions this study as a technologically and environmentally relevant solution.